Gut bacteria of animals/pests are potential source of antibacterial molecules(s) - Noor, Akbar (2019)
Infectious diseases, in particular bacterial infections are the leading cause of morbidity and mortality, posing a global threat to human health. The emergence of antibiotic resistance has exacerbated the problem further. The majority of antibiotics available in the market are produced by bacteria isolated from soil. However, the “low-hanging fruit” has been picked, hence there is a need to mine bacteria from unusual sources. With this in mind, it is important to note that animals and pests such as cockroaches, snake, crocodiles, water monitor lizard. come across pathogenic bacteria regularly yet flourish in contaminated environments. These species must have developed methods to defend themselves to counter pathogens. Although the immune system is known to possess anti-infective properties, gut bacteria of animals/pests may also offer a potential source of novel antibacterial(s) and it is the subject of this study. Herein, we explored gut bacteria of various animals/pests living in polluted environments for their antibacterial properties against multi-drug resistant pathogenic bacteria. A variety of animals/pests species were procured including invertebrate species, Blaptica dubia (cockroach), Gromphadorhina portentosa (cockroach), Scylla serrata (crab), Grammostola rosea (tarantula), Scolopendra subspinipes (centipede) and vertebrate species including Varanus salvator (water monitor lizard), Malayopython reticulatus (python), Cuora amboinensis (tortoise), Oreochromis mossambicus (tilapia fish), Rattus rattus (rat), Gallus gallus domesticus (chicken) and Lithobates catesbeianus (frog). Gut bacteria of animals/pests were isolated and identified using microbiological, biochemical and molecular identification methods. Bacterial conditioned media were prepared using Roswell Park Memorial Institute (RPMI) medium and tested against selected Gram-positive and Gram-negative pathogenic bacteria as well as human cells. The results revealed that conditioned media of gut bacteria exhibited significant broad-spectrum antibacterial activities. Upon heat inactivation, the conditioned media retained their antibacterial properties suggesting their nature as secondary metabolites and/or peptides. Conditioned media showed no or minimal cytotoxicity against human cells. To determine the identity of the active molecules, conditioned media were subjected to Liquid Chromatography Mass Spectrometry (LCMS). Tandem Mass Spectrometric analysis revealed the presence of various secondary metabolites belonging to flavonoids, terpenoids, alkaloids, polyhydroxy alkaloids, polyacetylenes, bisphenols, amides, oxylipin, pyrazine derivatives, a series of known as well as novel N-acyl-homoserine lactones, several homologues of 4-hydroxy-2-alkylquinolines, rhamnolipids, surfactin and Iturin A (lipopeptides) molecules. Selected purified molecules were tested against Gram-positive and Gram-negative bacteria and exhibited significant antibacterial properties. These outcomes are significant and provide the basis for rational development of therapeutic antibacterials. The molecular identity of the unidentified molecules in the conditioned media using analytical approaches, in vivo effects of the identified molecules together with their mode of action is the subject of future studies which could lead to the development of novel antibacterial(s).